Penanaman Nilai Kejujuran Saat Ujian Nasioal di SMK Nurul Iman Palembang - Liana, Disti (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2018)
Almost every year education in Indonesia is always shrouded in problems especially when national exam will be held. Problems that arise like cramming, compressing National Exam subjects by leaving other lessons, forming successful teams, and giving sanctions to Schools that fail the National Exam, and others. Supposedly, the National Exam is the answer in our efforts to realize an honest and achieving education process. This study aims to determine how the teachers efforts in inculcating the value of honesty during the National Examination at Vocational High School Nurul Iman Palembang. This research is a field research with qualitative approach. To obtain data in this research, researcher use some methods in collecting data that are observation, interview and documentation. Data analysis technique used is descriptive technique. The result of the research is the cultivation of honesty value during the National Exam in Vocational High School Nurul Iman Palembang, among others: First, appealed and advised the students to study hard at home and school and take the best time to learn. Second, hold impromptu evaluation. Third, cultivating faith in God confesses that there is no god but Allah, always remember Allah wherever located so afraid to commit sins or errors intentionally even if not known by others. Fourth, explain the honest benefits of the National Examination.